Novel mutations in the TBX5 gene in patients with Holt-Oram Syndrome - Porto, Marianna P. R. (Sociedade Brasileira de Genética, 2010)
The Holt-Oram syndrome (HOS) is an autosomal dominant condition characterized by upper limb and cardiac malformations. Mutations in the TBX5 gene cause HOS and have also been associated with isolated heart and arm defects. Interactions between the TBX5, GATA4 and NKX2.5 proteins have been reported in humans. We screened the TBX5, GATA4, and NKX2.5 genes for mutations, by direct sequencing, in 32 unrelated patients presenting classical (8) or atypical HOS (1), isolated congenital heart defects (16) or isolated upper-limb malformations (7). Pathogenic mutations in the TBX5 gene were found in four HOS patients, including two new mutations (c.374delG; c.678G > T) in typical patients, and the hotspot mutation c.835C > T in two patients, one of them with an atypical HOS phenotype involving lower-limb malformations. Two new mutations in the GATA4 gene were found in association with isolated upper-limb malformations, but their clinical significance remains to be established. A previously described possibly pathogenic mutation in the NKX2.5 gene (c.73C > 7) was detected in a patient with isolated heart malformations and also in his clinically normal father.